A coroação de Reis Negros e a tradição Congadeira: um elo entre o Velho e o Novo Mundo = The coronation of the Black Kings and the tradition of the Congado : a link between the Old and the New World - Rabello, Kelly (Numen, 2019)
Between the 16th and 19th centuries, Africans of Bantu origins were enslaved and forcibly brought to Brazil. Although much of their original customs were lost, through tools such as language, dance and music, these people were able to maintain some of their cultural practices, especially those that associated entertainment to religion. These elements notably came to life on festivities associated with religious Brotherhoods, in which black men and women practiced particular dance routines, chants and dances in homage to that brotherhood’s patron saint and enthroned their own kings. Composed by this set of rituals, the Congado showed characteristics of a peculiar black Catholicism. Practiced even nowadays, the Congado and the Reinado still tell us much about the post diaspora dynamics and the means of adaptation and resistance of black people in Brazil. The aim of this paper is to reflect about the importance of the Congados and Reinados as manifestations that guard an ancestral memory. The methodology consists in a bibliographic review of the thematics of African Catholicism, Black Catholicism, Black Brotherhoods and Congado.